Investigation of current threats to the existence of Brackenridgea zanguebarica in a small geographic area in Vhembe, Limpopo Province, South Africa - MAKUÉTÉ ANDRÉ PATRICK TIAWOUN; MILINGONI PETER TSHISIKHAWE; EASTONCE TENDAYI GWATA (Society for Indonesian Biodiversity, 2019)
Abstract. Tiawoun MAP, Tshisikhawe MP, Gwata ET. 2019. Geometric morphometry of pupae to identify four medically important flies (Order: Diptera) in Thailand. Biodiversitas 20: 1504-1509. Brackenridgea zanguebarica is one of the most threatened plant species in South Africa, found only in Thengwe village, Vhembe District Municipality, Limpopo Province, South Africa. Due to the high traditional use of its stem bark and root, the species is now facing the threat of extinction. It has been assessed in accordance with the IUCN Red List of South Africa as a critically endangered species. The aim of this study was to investigate the impact of current threats to the population in the Brackenridgea Nature Reserve, in order to improve its conservation measures. The study was carried out in the reserve, where 10 belt transects of 50 m long and 20 m wide were laid at regular intervals of 5 m to investigate the population of B. zanguebarica. Individuals were counted and the structural parameters, e.g. tree height and stem diameter size of each were measured, while the impact of plant harvesting was estimated using a sliding scale of 0 to 5. The structure of the populations in terms of the stem diameter size classes was dominated by juvenile plants that showed the bell shape pattern. In addition, 59.9% out of the total plants recorded presented signs of plant parts extraction, with the stem bark the main part extracted. The population status of B. zanguebarica was unstable and under severe threat due to the destructive harvesting of the mature tree parts, leading to poor regeneration of individuals. It is thus recommended that in order to improve its conservation measures.